Avaliação da atividade antimicrobiana, antibiofilme e citotoxicidade do óleo essencial de Cymbopogon martinii frente a Staphylococcus aureus - Lara, Anne Lima de (2023)
The biofilm is characterized as a community of microorganisms adhered to a surface, which gives microbial cells protection against external agents, characterizing itself as an important form of resistance. In hospitals, they represent a large part of infections related to catheters and other invasive medical devices. Staphylococcus aureus is an opportunistic Gram-positive bacterium, commonly present in the skin and nasal cavities of healthy individuals, which can cause from mild infections to sepsis, being more found in skin infections, and frequently in nosocomial infections, and also has the ability to form of biofilm. Currently, the multidrug resistance of S. aureus to antimicrobials leads to the search for alternatives for the treatment of infections and, in this context, is the essential oil of Palmarosa (Cymbopogon martinii). It is a plant from India, and its essential oil is widely used in the cosmetics and perfumery industry. It has antibacterial and antifungal activity, with great antibiofilm potential. Therefore, this work aimed to evaluate the antimicrobial effect, antibiofilm and in vitro toxicity of the essential oil of C. martinii with emphasis on S. aureus. For this, the characterization of the essential oil was carried out, whose main compound detected was geraniol (83.8%), and the disc-diffusion techniques; microdilution (minimum inhibitory and bactericidal concentration); formation and treatment of biofilms; determination of biofilm biomass; quantification of viable cells in the biofilm; and activity kinetics in formed biofilm. The results demonstrate a significant action in reducing the biofilm of Staphylococcus aureus (ATCC 29213 and clinical isolates), as well as Escherichia coli (ATCC 25922), Enterococcus faecalis (ATCC 51299) and Streptococcus mutans (ATCC 25175). In addition, safety was also evaluated through MTT, nitric oxide, DCFHDA and Picogreen assays, which proved to be suggestive of toxicity in fibroblasts, keratinocytes, and peripheral blood mononuclear cells.